Penetapan Daluwarsa dalam Pertanggungjawaban Notaris Terhadap Akta yang Dibuatnya - Eunice Primsa Munthe (Universitas Medan Area, 2020)
Notarial Act (UUJN-P) does not stipulate the perimeters of notaries’ liability concerning the deeds they have drafted, resulting uncertainty to notaries or retired notaries that they are shadowed for life by sentences that can be imposed anytime. This is a normative juridical research with analytical description. It uses primary data collected from interviews with two notaries, and secondary data collected from primary, secondary, and tertiary legal materials. Article 1967 of the Civil Code states that the time period of an expiration date was 30 years. Meanwhile, Article 78 paragraph (1) number 3 states that lawsuits in a penal case are expired in twelve years. The form of notaries’ liability for provisions of the expiration dates that cannot be implemented for the deeds they have drafted have to still be liable in civil law, penal law, Regulations on Notary Position concerning material authenticity, and the code of ethics of notaries in performing their duties. That there is not any provisions in the Notarial Act that regulate notaries’ liability after they completed their term of office.The provisions on expiration dates of notaries’ liability are not assertively stipulated in the Civil Code, but there is not any provisions on its enactment to notaries as a legal subject. It is recommended that more specific provisions be made to regulate the expiration dates. It is suggested that the goverment of Indonesian create a particular regulation concerning the limitations of notaries’ liability for the deeds that they have drafted after their term of office ends. It is also suggested that notaries be truthful, conscientious, independent and impartial in drafting deeds and providing services, and comprehend as well as have knowledge of provisions in the prevailing laws and regulations, propriety, and morality.